2015
DOI: 10.1007/s00436-015-4845-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of camel trypanosomosis (surra) and associated risk factors in Borena zone, southern Ethiopia

Abstract: A study was made to determine the prevalence of camel trypanosomosis (surra) and its associated risk factors in Borena zone, southern Ethiopia during 2013-2014. A total of 2400 blood samples were collected and examined by the buffy coat and thin blood film laboratory methods, and data were analyzed using the SPSS statistical software. The overall prevalence of camel trypanosomosis in the area was found to be 2.33 %. Prevalence was significantly different among the surveyed districts (P = 0.000), the pastoral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
5
10
2
Order By: Relevance
“…No effect of camel age on T. evansi seropositivity was observed in our study. Our finding agrees with some surveys (Boushaki et al 2019;Pathak & Khanna 1995;Shah et al 2004), but differs from those of other research groups who reported increased seroprevalence with increasing age (Atarhouch et al 2003;Bogale et al 2012;Dia et al 1997;Eshetu, Desta & Amare 2013;Gutierrez et al 2000;Mirshekar, Yakhchali & Shariati-Sharifi 2017;Olani et al 2016;Tehseen et al 2015). In contrast to the above findings, one study in Ethiopia revealed higher infection rates in younger camels than in older adult camels (Lemecha, Lidetu & Hussein 2008).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…No effect of camel age on T. evansi seropositivity was observed in our study. Our finding agrees with some surveys (Boushaki et al 2019;Pathak & Khanna 1995;Shah et al 2004), but differs from those of other research groups who reported increased seroprevalence with increasing age (Atarhouch et al 2003;Bogale et al 2012;Dia et al 1997;Eshetu, Desta & Amare 2013;Gutierrez et al 2000;Mirshekar, Yakhchali & Shariati-Sharifi 2017;Olani et al 2016;Tehseen et al 2015). In contrast to the above findings, one study in Ethiopia revealed higher infection rates in younger camels than in older adult camels (Lemecha, Lidetu & Hussein 2008).…”
Section: Discussionsupporting
confidence: 82%
“…Worldwide, several authors have reported considerable differences in the seroprevalence of T. evansi in different geographical areas within the same country (Aregawi et al 2015;Bogale et al, 2012;Delafosse & Doutoum 2004;Dia et al 1997;Mirshekar et al 2017;Olani et al 2016;Salah, Robertson & Mohamed 2019;Tehseen et al 2015). In most cases, these within country differences can be explained by the observed variation in ecological factors (e.g., pastoral camel densities, hottest, most humid and wettest districts in the region) that affect vector densities and therefore infection prevalence (Hagos et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…of studiesHost c No. of studies per hostDetection methodsReferencesAfricaAlgeria2Camel1Stained blood smear[89]Horse1Unspecified microscopic method[90]Chad1Camel1HCT and PCR[91]Egypt13Buffalo1CATT[82]Camel10Stained blood smear, mouse inoculation, CATT, ELISA, Suratex, Latex, thymol turbidity, PCR[1, 77, 92–99]Cattle2ELISA, PCR[100, 101]Goat1Stained blood smear, CATT, PCR[96]Sheep1Stained blood smear, CATT, PCR[96]Human1Stained blood smear, ELISA[77]Ethiopia a 8Camel8Stained blood smear, HCT, CATT, ITL, PCR[83, 102108]Cattle1HCT, CATT, PCR[83]Donkey1CATT, ITL, PCR[83]Goat1HCT, CATT, ITL, PCR[83]Horse1PCR[83]Mule1PCR[83]Sheep1HCT, CATT, ITL, PCR[83]Ghana b 1Tsetse fly1PCR[30]Kenya9Camel9HCT, mouse inoculation, CATT, ELISA, Suratex, Latex, IHA, PCR[13, 109116]…”
Section: Resultsmentioning
confidence: 99%
“…From a total of 69 full text studies accessed, we removed nine of them because the outcome of interest was not mentioned and/or they were conducted in other nations which are not the location of interest of the review; these studies were conducted in Africa 69,70 , Tanzania 71,72 , Malawi 73 , Nigeria [74][75][76] and Mali 77 . In addition, 20 full text articles [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] that have been carried out from different parts of Ethiopia were excluded because their outcome measures were not prevalence of anemia in children, and they were conducted in the adult population which is not the population of interest of the this meta-analysis. Moreover, one full text article 98 was excluded because of duplicated publications of our result of interest in different journals (see additional file 3).…”
Section: Search Resultsmentioning
confidence: 99%